Synthesis of ternary SnO2–MoO3–C composite with nanosheet structure as high-capacity, high-rate and long-lifetime anode for lithium-ion batteries. Issue 7 (1st April 2021) - Feng, Yefeng; Wu, Kaidan; Ke, Jin; Guo, Zhiling; Deng, Xiaoqian; Bai, Chen; Sun, Yukun; Wang, Qiao; Yang, Bingwen; Dong, Huafeng; Xiong, Deping; He, Miao
Abstract: The SnO2 –MoO3 –C composite anode for Li-ion batteries (LIBs) was produced via simple hydrothermal synthesis and dry ball milling. In this hybrid, nanosized-SnO2 /MoO3 nanoparticles were encapsulated in plate-like graphite. MoO3 additive can protect Sn from aggregating and accelerate the reversible conversion reaction (Sn/Li2 O hybrid transformation into SnO2 ). The SnO2 –MoO3 –C displays high initial coulombic efficiency of 70% (average for five cells), high reversible specific capacity of 1338.3 mAhg −1 at 0.2 A g -1 after 300 cycles, superior rate capacity of 715.08 mAhg −1 at 5 A g -1 and long-term cyclic stability, with capacity of 571.9 mAhg −1 at 2.0 A g -1 after 1000 cycles. Owing to its superior performance and simple synthesis, the SnO2 –MoO3 –C composite is a promising anode material for LIBs.